Detection of VipAlbumin® Effect in CD34 and SDF-1 Mobilization, in Streptozotocin-induced Diabetes Mellitus Mice - Pradana, Andi Rizki Adi; Djati, Muhammad Sasmito; Rifa'i, Muhaimin (The Journal of Experimental Life Science, 2015)
Diabetes mellitus is a disease in which the body loses its ability to provide tight regulation and maintain a dynamic interaction between the tissue sensitivity and insulin secretion by β cells. The impact of this dysfunctional mechanism is uncontrolled blood glucose levels that lead to hyperglycemia condition. Highly reactive free radicals have a strong involvement in the pathogenesis of diabetes mellitus, where one of its forming process may be triggered by hyperglycemia condition. Patients with diabetes mellitus itself vulnerable to endothelial dysfunction, which is caused by a decrease in circulating endothelial progenitor cells, and also a decrease in chemokines which play a role in affecting the activities of these cells. Hyperglycemia condition and free radical activity is a major cause of these endothelial progenitor cells dysfunction.The purpose of this study was to determine the role of VipAlbumin®, a supplement derived from Channa striatus albumin extracts in inhibiting the action of free radicals that are formed due to hyperglycemia condition, which can affect the increase in endothelial progenitor cells relative amount. This study used BALB/C mice that induced to undergo diabetes mellitus through streptozotocin injection intraperitoneally at 5-day old. Mice who have reached 4 week old and positive to diabetes mellitus (blood glucose levels > 200 mg.dl-1) will be administered with VipAlbumin® orally for 14 days. VipAlbumin® dosage was divided into 4 groups: positive control (without VipAlbumin®); 1st dose (0.01664 mg.gr-1 BW); 2nd dose (0.416 mg.gr-1 BW); 3rd dose (10.4 mg.gr-1 BW). The last step was flow cytometric analysis to determine the development of endothelial progenitor cells relative amount, which isolated from bone marrow. The variables measured in this study were the relative amount of CD34+ and SDF-1. Based to flow cytometric analysis, mice with VipAlbumin® administration did not show any significant improvement in CD34 relative amount when compared to the positive control. Relative amount of Chemokine SDF-1 itself, although only occur at the 3rd dose of VipAlbumin® treatment, has increased and significantly different from the positive control. Keywords: CD34, diabetes mellitus, free radicals, hyperglycemia, SDF-1, streptozotocin, VipAlbumin®